1995
DOI: 10.1182/blood.v86.9.3567.bloodjournal8693567
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Lyn is a common element of the stimulation of human neutrophils by soluble and particulate agonists

Abstract: The functional responsiveness of human neutrophils is known to be initiated and modulated by protein tyrosine phosphorylation. The regulation of the levels of tyrosine phosphorylation is most likely the result of the coordinated actions of tyrosine kinases and phosphatases, which have so far been only very partially characterized. In the present study, we present evidence demonstrating that the stimulation of neutrophils by a variety of agonists (soluble as well as particulate) leads to the activation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 66 publications
3
19
0
Order By: Relevance
“…Activation of plasma membrane heterotrimeric G proteins, of protein kinase C (PKC), and of Src family kinases is among a variety of the known crystal-induced upstream signals potentially able to promote rapid acti-vation of ERK-1/ERK-2 (1,13,(23)(24)(25)(26)50). Significantly, hydroxyapatite crystal-induced and triclinic CPPD crystal-induced ERK-1/ERK-2 activation mediates crystal-induced mitogenesis in foreskin fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of plasma membrane heterotrimeric G proteins, of protein kinase C (PKC), and of Src family kinases is among a variety of the known crystal-induced upstream signals potentially able to promote rapid acti-vation of ERK-1/ERK-2 (1,13,(23)(24)(25)(26)50). Significantly, hydroxyapatite crystal-induced and triclinic CPPD crystal-induced ERK-1/ERK-2 activation mediates crystal-induced mitogenesis in foreskin fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory crystals, like growth factors, activate multiple transduction pathways, including heterotrimeric and ras superfamily G proteins, phospholipases A 2 , C, and D, the Src family tyrosine kinases, and NADPH oxidase (1,(23)(24)(25)(26)(27)(28)(29). MAPK activation has been documented in certain cell types in the context of crystal-induced signal transduction, and a role demonstrated for certain cell functions.…”
mentioning
confidence: 99%
“…We highlight here several of the most reported ones. Src family kinase member Lyn is activated in human neutrophils by MSU crystals (62). Using the human monocytic cell line THP-1, Liu et al (21) reported that MSU stimulation led to the activation of c-Src, Lyn, Hck, and Fyn, as well as serine ⁄ threonine kinase p70s6k.…”
Section: Other Kinasesmentioning
confidence: 99%
“…The non-receptor tyrosine kinases Fgr [36], Hck [37], Syk [38], and Lyn [39] have been shown to be activated by fMLP. Vanadate has also been shown to activate Btk, Hck, and Syk [40].…”
Section: Discussionmentioning
confidence: 99%